A Quiet Harbour: Finding a Balanced Approach to the Copyright Liability of Online Service Providers - Sam Alexander (Bond Law Review)
The United States, via the Online Copyright Infringement Liability Limitation Act, provides a safe harbour from copyright liability for online service providers. This safe harbour has been described as one of the laws that ‘built’ Silicon Valley. Despite the experience in the United States, Australia has not extended its own copyright safe harbour provisions to online service providers. This article seeks to understand the underlying reasons for such different approaches by adopting a comparative analysis methodology. After reviewing the legislative history and case law in the United States and in Australia, this article presents evidence suggesting copyright safe harbours support innovation. As such, this article contends there is a need to reconsider the scope of Australia’s copyright safe harbour. However, it is also demonstrated that the approach taken by the United States has not been without its flaws and, therefore, rather than a complete adoption of this position, Australia should consider a more ‘balanced’ approach—namely, extending the copyright safe harbour, while also introducing amendments to bring clarity and balance to the safe harbour provisions.